2019
DOI: 10.1016/j.xphs.2018.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Polymer Loading on Dissolution Behavior of Amorphous Griseofulvin Powder

Abstract: The effect of particle size on the dissolution behavior of the particles of amorphous solid dispersions (ASDs) of griseofulvin (GF), with 0%-50% Kollidon ® VA 64 as a crystallization inhibitor is investigated. Both the final dissolved GF concentration and the dissolution rate of GF ASDs were found to be inversely proportional to the particle size. The solution concentrations for the smallest (45-75 mm) size group with different polymer loadings were significantly higher than those for the largest (250-355 mm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Unlike for the ASDs, the matrix size/surface area impact does not seem to be remarkable for the nanocomposites because the observed lower extent of GF dissolution was mostly controlled by the lower thermodynamic solubility of the nanocrystalline drug itself (Figure 7c-f). Our findings agree well with the findings from a recent study by Zhang et al [56], wherein 25% proprietary drug-loaded HPMCAS-(hydroxypropyl methylcellulose acetate While full release of the drug is important for achieving a desired pharmacokinetic profile and ensuring complete utilization of the drug dose, immediate release (80% drug released in 30 min) is not a requirement for solid dosages containing poorly soluble drugs and it may not even be achievable (e.g., [57,99]), and/or desirable except for therapeutic indications where a rapid onset of action is required, for example, pain management [100]. In this study, although GF is an antifungal drug, immediate release from the 10% GF loaded, milled extrudates was regarded to be "desirable" within the context that a higher GF loading could cause a significant dissolution slow-down [57] (see also Section 3.5).…”
Section: Impact Of Matrix Surface Area At the Supersaturating Dissolution Conditionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike for the ASDs, the matrix size/surface area impact does not seem to be remarkable for the nanocomposites because the observed lower extent of GF dissolution was mostly controlled by the lower thermodynamic solubility of the nanocrystalline drug itself (Figure 7c-f). Our findings agree well with the findings from a recent study by Zhang et al [56], wherein 25% proprietary drug-loaded HPMCAS-(hydroxypropyl methylcellulose acetate While full release of the drug is important for achieving a desired pharmacokinetic profile and ensuring complete utilization of the drug dose, immediate release (80% drug released in 30 min) is not a requirement for solid dosages containing poorly soluble drugs and it may not even be achievable (e.g., [57,99]), and/or desirable except for therapeutic indications where a rapid onset of action is required, for example, pain management [100]. In this study, although GF is an antifungal drug, immediate release from the 10% GF loaded, milled extrudates was regarded to be "desirable" within the context that a higher GF loading could cause a significant dissolution slow-down [57] (see also Section 3.5).…”
Section: Impact Of Matrix Surface Area At the Supersaturating Dissolution Conditionsupporting
confidence: 91%
“…More importantly, the impact of matrix size in various sieved size fractions on drug release has not been extensively examined and related to the specific surface area of the respective size fractions. Two recent studies [ 56 , 57 ] regarding matrix size effect on drug release from ASDs prepared by HME and melt-quenching will be discussed in Section 3.4 of this paper. When nanocomposites were produced by nanoextrusion, the impact of matrix size has not been investigated [ 40 , 47 ] or has not been examined extensively and systematically and analyzed for multiple size fractions and drug loadings [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2018) compared very fine ASD particles obtained by spray-drying with coarse ASD particles obtained by hot-melt extrusion and they found that the production technique profoundly impacted the dissolution properties (29). Zheng et al (2019) showed that the dissolution rate were inversely proportional to the particle size (30). However, also the recrystallization kinetics were dependent on the particle size since the extent of supersaturation and the supersaturation generation rate are determinative for the nucleation rate (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…However, the placebo extrudates dissolved relatively faster than the IND ASDs at a respective pH. This is quite plausible due to the fact that the presence of a drug with a considerably high logP value (4.3) within the polymeric carrier increases the lipophilicity of the drug-containing ASD compared to the pure polymer [27,28]. Consequently, the increased lipophilicity led to a slower dissolution rate for the drug-containing ASD.…”
Section: Non-sink Dissolutionmentioning
confidence: 98%
“…Zhang et al (2018) showed that the particle size profoundly impacted the performance of an ASD, where a moderate particle size was superior to very fine powder due to the avoidance of a premature release of the weakly basic drug. Zheng et al (2019) observed that finer ASD particles tended towards faster recrystallization as compared to more coarse particles [27,28].…”
Section: Introductionmentioning
confidence: 97%